Priority Setting in Health Care: A Complementary Approach - Nunes, Rui (Springer US, 2013)
Explicit forms of rationing have already been implemented in some countries, and many of these prioritization systems resort to Norman Daniels’ “accountability for reasonableness” methodology. However, a question still remains: is “accountability for reasonableness” not only legitimate but also fair? The objective of this paper is to try to adjust “accountability for reasonableness” to the World Health Organization’s holistic view of health and propose an evolutionary perspective in relation to the “normal” functioning standard proposed by Norman Daniels. To accomplish this purpose the authors depart from the “normal” functioning standard to a model that promotes effective opportunity for everyone in health care access, because even within the “normal” functioning criteria some treatments and medical interventions should have priority upon others. Equal opportunity function is a mathematical function that helps to hierarchize moral relevant necessities in health care according to this point of view. It is concluded, first, that accountability for reasonableness is an extremely valuable tool to address the issue of setting limits in health care; second, that what is called in this paper “equal opportunity function” might reflect how accountability for reasonableness results in fair limit-setting decisions; and third, that this methodology must be further specified to best achieve fair limit-setting decisions. Indeed, when resources are especially scarce the methodology suggested in this paper might allow not only prioritizing in an “all or nothing” basis but can contribute to a hierarchy system of priorities in health care.